Realitas atau Harapan: Co-Creation dalam Penciptaan Pengalaman Berkualitas di Desa Wisata Panglipuran, Bali - Pangastuti, Diana Putri; Gunadi, I Made Adhi; Octavanny, Vitha (Gadjah Mada Journal of Tourism Studies, 2025)
This research aims to identify Co-Creation within the Service Dominant Logic approach and analyze it’s influence on Tourist Experience in Penglipuran Tourism Village, Bali. This research uses quantitative descriptive research method. The independent variables of Co-Creation in this study are participation, personalization, interaction, and involvement, while the dependent variable is Tourist Experience. The sample gained 117 respondents with purposive sampling techniques. Through implementation of Co-Creation, showing that the personalization variable bring deep impression for the tourist because of the authenticity of the culture and traditions displayed; on the involvement variable, tourists are enthusiastic about learning the local customs of Penglipuran; on the participation variable, tourists feel a deep cultural experience as they participate in meaningful tourism activities; whilst on the interaction variable, tourists actively interact directly with local residents. The variable of Tourist Experience shows that tourists gain a lot of inspiration and overall tourists get satisfying experience from the services, activities and amenities. Analyzing the impact showed that Co-Creation simultaneously has a positive and significant influence toward Tourism Experience, while partially variables of personalization and involvement have an influence on Tourist Experience. This left two other variables, which is participation and interaction have no effect on the tourist experience.